ANALISIS PENDAPATAN DAN PEMASARAN TAHU PADA INDUSTRI âAFIFAHâ DI KOTA PALU SULAWESI TENGAH - Narmin, Narmin; Antara, Made (AGROTEKBIS, 2016)
The agriculture and industry sectors are interrelated sectors, where agriculture is the provider of raw materials, while the industry processes the agricultural products to obtain added values. Small industries are very large parts of an economy. Some small industries are potential to be developed, one of which is tofu business. Central Sulawesi was one of suitable areas for soybean development. Some areas in Central Sulawesi had been processing the soybean plant, but they were only intended for sale and consumption. The entrepreneurs and businessmen in Palu City have begun to see these opportunities and developed agro-industry by processing soybeans into tofu. This study was conducted at âAfifahâ Tofu Industry in Jl. Jati No. 08 Nunu Village Tatanga District Palu City, Central Sulawesi. This study aimed 1) to determine the form of marketing channel of âAfifahâ Tofu Industry, and 2) to determine the marketing margin of âAfifahâ Tofu Industry. Respondent determination was purposively selected including one chairman of âAfifahâ Tofu Industry, one worker of âAfifahâ Tofu Industry, and six tofu traders. The results showed that the revenue earned in September 2015 was IDR 7,219,206.Â There were two forms of marketing channel at âAfifahâ Tofu Industry, namely 1) the producer sold its products to the retailers then the retailers sold them to the last consumers, and 2) the producer sold its products directly to the last consumers. Tofu marketing margin gained at the first channel was IDR 33,000, while there was no margin at the second channel because the producer sold its products directly to the consumers.Â Key Words: Income, marketing channel, marketing margin, and tofu.